1989
DOI: 10.1111/j.1360-0443.1989.tb00551.x
|View full text |Cite
|
Sign up to set email alerts
|

The Sex Industry, Alcohol and Illicit Drugs: implications for the spread of HIV infection

Abstract: Summary A review is presented of the association between the sex industry and the use and misuse of alcohol and illicit dmgs. It is concluded that both the latter are associated with 'high risk' sexual activities and that heavy drinking and illicit drug use are commonplace amongst prostitutes and their clients. Outside Africa evidence suggests that in some, though by no mearts all, areas prostitutes have low or zero levels of HIV seropositivity. It is concluded that far more information is needed on the patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 39 publications
1
29
0
1
Order By: Relevance
“…FSW-IDUs were almost seven times more likely to use illicit drugs before sex than other FSWs. This is troubling because sex work conducted under the influence of drugs has been associated with lower rates of condom use in other settings (Plant et al, 1989, Paone et al, 1999, de Graaf et al, 1995. In a study conducted in the United Kingdom (Gossop et al, 1995), FSWs' drug use was associated with having unprotected sex with clients in exchange for more money, which is not surprising since women suffering from withdrawal symptoms may be more likely to acquiesce to demands for unsafe sex to support their drug habit.…”
Section: Discussionmentioning
confidence: 98%
“…FSW-IDUs were almost seven times more likely to use illicit drugs before sex than other FSWs. This is troubling because sex work conducted under the influence of drugs has been associated with lower rates of condom use in other settings (Plant et al, 1989, Paone et al, 1999, de Graaf et al, 1995. In a study conducted in the United Kingdom (Gossop et al, 1995), FSWs' drug use was associated with having unprotected sex with clients in exchange for more money, which is not surprising since women suffering from withdrawal symptoms may be more likely to acquiesce to demands for unsafe sex to support their drug habit.…”
Section: Discussionmentioning
confidence: 98%
“…As a hidden and lucrative industry, commercial sex is increasing globally 20 and has social characteristics that tend to influence both drinking and smoking. [21][22][23] Brothels may serve as outlets which promote the sale and use of alcohol and tobacco products.…”
Section: Introductionmentioning
confidence: 99%
“…'7-24 Previous research has also documented associations between psychological distress and dependence on opiates25'26 and alcohol,27'28 both of which are also associated with sex trading. [29][30][31][32][33][34] Previous studies have also found associations between psychological distress and knowledge of HIV infection35-38 and the perception of risk for acquired immunodeficiency syndrome (AIDS).39…”
Section: Introductionmentioning
confidence: 99%